Estimativa de variáveis de estado na termometria por ressonância magnética aplicada ao tratamento de tumores - César Cunha, Pacheco (2018)
Promising advances have been achieved in the field of hyperthermia treatment for tumors in the recent years; however, a successful treatment in this particular area is profoundly associated with reliable techniques for quantifying the temperature distribution in the biological tissue being treated. The advancement in thermometry techniques using magnetic resonance presents itself as an alternative for health professionals to perform this task; however, some limitations are still present, such as the difficulty in measuring absolute temperature in tissue — limiting the physician to measure only the local temperature rise; and the uncertainties in important physiological parameters, from different factors, including intrinsic differences between patients. This work seeks to develop a computer algorithm capable of, while obtaining measurements from the magnetic resonance device, calculating the temperature within the tissue through the joint application of mathematical models for heat conduction and uncertainty quantification techniques. It is expected that this algorithm help health professionals to obtain more reliable information, allowing the broadening of the range of possibilities for hyperthermia treatment.